Application of socio-technical systems models to Martian colonisation and society build. (3rd March 2020) - Braddock, Martin; Wilhelm, Christian Peter; Romain, Adam; Bale, Lee; Szocik, Konrad
Abstract: The human desire for exploration, together with an increasingly demanding potential need for establishing a human colony away from Earth has stimulated the concept and early planning for Mars colonisation. Successful delivery of such a challenging and expensive technological feat requires a highly informed and supportive general society. Although the ergonomic constraints on astronauts living and working in space is well documented, no study has employed the use of ergonomics tools to explore colony and societal build on other worlds. We have employed Cognitive Work Analysis to derive an abstraction hierarchy for both colony establishment and maintenance with the vision of building a new Martian society. We find that our model will accommodate five major challenge themes collected from over 800 members from twenty two United Kingdom - based astronomical societies and scientific groups and propose that this study may have utility in guiding mission planners in the early colonisation phase and later stage expansion processes. Using the proposed architecture for the Mars One mission, we have performed a basic human factors analysis and propose a number of key design features which may enable long term habitation.